2022
DOI: 10.1097/pcc.0000000000003117
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Corticosteroids and Pediatric Sepsis Biomarker Risk Model (PERSEVERE)-II Biomarker Risk Stratification With Mortality in Pediatric Septic Shock*

Abstract: OBJECTIVES: Mortality risk stratification may identify a subset of children who benefit from or are harmed by corticosteroid administration. The Pediatric Sepsis Biomarker Risk Model (PERSEVERE)-II score is a biomarker-based mortality risk stratification tool for pediatric sepsis. Our objective was to assess the association of corticosteroid administration with 28-day mortality within different levels of baseline mortality risk (PERSEVERE-II) in a cohort of children with septic shock. DESIGN:We performed a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The taskforce described its idea for identifying phenotypes associated with poor outcome and the relative merits of using clinical scoring of concurrent organ system dysfunction versus using serum biomarker evaluation in this analysis. Regarding biomarkers, the recent research narrative in PCCM has covered two extremes in approach: a multi-biomarker stratification tool as used in the Pediatric Sepsis Biomarker Risk Model (PERSEVERE I and II) panel of systemic inflammatory cytokines (14, 15); and a more reductionist (and likely more feasible—in my opinion) tool using just ferritin alone or in combination with C-reactive protein level (16–18).…”
Section: What About the Feasibility Of Biomarker-based Risk Stratific...mentioning
confidence: 99%
“…The taskforce described its idea for identifying phenotypes associated with poor outcome and the relative merits of using clinical scoring of concurrent organ system dysfunction versus using serum biomarker evaluation in this analysis. Regarding biomarkers, the recent research narrative in PCCM has covered two extremes in approach: a multi-biomarker stratification tool as used in the Pediatric Sepsis Biomarker Risk Model (PERSEVERE I and II) panel of systemic inflammatory cytokines (14, 15); and a more reductionist (and likely more feasible—in my opinion) tool using just ferritin alone or in combination with C-reactive protein level (16–18).…”
Section: What About the Feasibility Of Biomarker-based Risk Stratific...mentioning
confidence: 99%
“…It is likely that a truly definitive answer to this question remains elusive because of the heterogeneity of the sepsis population (4,5). Accordingly, the article by Klowak et al (6) published in this issue of Pediatric Critical Care Medicine is of interest, as it reports results of a retrospective descriptive investigation examining the association of corticosteroid administration with 28-day mortality for a cohort of children with septic shock exhibiting differential baseline mortality risk assessed by PEdiatRic SEpsis bio-markEr Risk modEl (PERSEVERE)-II, a biomarker-based stratification tool for (pediatric) sepsis. This article (6) and the corresponding secondary analysis of a multicenter observational study is notable in three regards: 1) It provides an excellent example of an iterative, rigorous clinical research program; 2) It escalates concern regarding knee-jerk prescription of corticosteroids for pediatric sepsis; and 3) It encourages development of real-time protein and messenger RNA (mRNA) quantification tools to facilitate clinical decision making around corticosteroid prescription for septic shock.…”
mentioning
confidence: 99%
“…Multiple previous observational studies have reported no benefit or potential harm associated with prescription of corticosteroids for pediatric septic shock; reviewed (2). In a previous analysis of 496 children with septic shock, Klowak et al (6) did not identify an association between corticosteroid administration and mortality when stratifying by PERSEVERE-I (21). As outlined above, however, the PERSEVERE-II biomarker, with inclusion of platelet count, has improved prognostic accuracy compared with PERSEVERE-I.…”
mentioning
confidence: 99%
See 2 more Smart Citations